Role of hydrogen peroxide in loss of culturability mediated by visible light in Escherichia coli in a freshwater ecosystem. - Arana, I (1992)
A study was made of the mechanisms by which visible light produces cell dormancy in Escherichia coli, resulting in loss of culturability. Visible light may act directly on the cells or generate photoproducts with a negative effect on the cells. In nonilluminated microcosms the addition of increasing concentrations of hydrogen peroxide, one of the photoproducts formed in natural aquatic systems, gave rise to the formation of nonculturable cells and injured culturable cells, and this negative effect depended on the concentration of peroxide. On the other hand, in illuminated microcosms the addition of compounds which eliminate hydrogen peroxide (i.e., catalase, sodium pyruvate, and thioglycolate) had a protective effect on the E. coli cells, as the CFU counts on minimal medium and on recuperation medium were significantly higher (P < 0.05) than those detected in the absence of these compounds. Furthermore, when hydrogen peroxide was eliminated, the CFU counts on recuperation medium did not fall significantly, indicating that nonculturable cells did not form. These results rule out the direct effect of visible light on the cells and show that hydrogen peroxide, generated photochemically, may be the cause of the loss of culturability of E. coli in illuminated systems.